Does sodium oxybate inhibit brain dopamine release in humans? An exploratory neuroimaging study. (26th April 2021) - Kish, Stephen J; O'Leary, Gerald; Mamelak, Mortimer; McCluskey, Tina; Warsh, Jerry J; Shapiro, Colin; Bies, Robert; Yu, Yifan; Pollock, Bruce; Tong, Junchao; Boileau, Isabelle
Abstract: Objective: To establish in an exploratory neuroimaging study whether γ‐hydroxybutyrate (sodium oxybate [SO]), a sedative, anti‐narcoleptic drug with abuse potential, transiently inhibits striatal dopamine release in the human. Methods: Ten healthy participants (30 years; 6M, 4F) and one participant with narcolepsy received a baseline positron emission tomography scan of [C‐11]raclopride, a D2/3 dopamine receptor radioligand sensitive to dopamine occupancy, followed approximately one week later by an oral sedative 3g dose of SO and two [C‐11]raclopride scans (1 h, 7 h post SO). Plasma SO levels and drowsiness duration were assessed. Results: No significant changes were detected in [C‐11]raclopride binding in striatum overall 1 or 7 h after SO, but a small non‐significant increase in [C‐11]raclopride binding, implying decreased dopamine occupancy, was noted in limbic striatal subdivision at one hour (+6.5%; p uncorrected = 0.045; +13.2%, narcolepsy participant), returning to baseline at 7 h. A positive correlation was observed between drowsiness duration and percent change in [C‐11]raclopride binding in limbic striatum ( r = 0.73; p = 0.017). Conclusions: We did not find evidence in this sample of human subjects of a robust striatal dopamine change, as was reported in non‐human primates. Our preliminary data, requiring extension, suggest that a 3g sedative SO dose might cause slight transient inhibition of dopamine release in limbic striatum.